Estudio de almacenamiento para determinar la vida útil de una Bebida de Chonta (bactris gasipaes) fermentada de bajo contenido alcohólico. - Cola Caiza, Magaly Maricela (2020)
The present investigation of the storage study to determine the shelf life of a chonta beverage (Bactris gasipaes) fermented with low alcoholic content, was carried out with the objective of establishing; the heat treatment, the type of container suitable for packaging the beverage, the correct temperature for storage, the different laboratory analyzes that can be performed to the beverage and implement a methodological guide that serves as a support instrument for the storage of chonta beverage to determine its shelf life. For which a bibliographic investigation of different investigative works already developed was carried out; through the information obtained, was determined that for the heat treatment, the fermented drink will be subjected to 65 ° C for at least 30 minutes and at 75 ° C for a maximum of 15 minutes, at a lower temperature a longer time and a higher temperature less time, avoiding exceeding the time and temperature limits. The right packaging for storing the fermented drink is the glass container as it helps to preserve the quality of the drink without affecting its organoleptic properties. The indicated storage temperature is of refrigeration at a temperature; as a minimum of 5 ° C and a maximum of 10 ° C, since at higher temperatures the fermentation of the beverage is faster. The most common physicochemical parameters to evaluate the chonta fermented drink are: pH, acidity, ° Brix, ° alcohol, microbiological analysis: mesophilic aerobes; molds and yeasts, sensory analysis and a bromatological analysis will be carried out to know the nutritional value of the beverage. The manual will help to evaluate the chicha in its storage, during which laboratory processes will be carried out, which are written within the manual with their respective methodology, with the main objective of knowing the useful life of the chonta drink.